2008
DOI: 10.1007/s10620-008-0534-1
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Endoscopic Papillary Balloon Dilatation Following Limited Sphincterotomy for Common Bile Duct Stones

Abstract: Endoscopic papillary balloon dilatation (EPBD) has been recently used in conjunction with endoscopic sphincterotomy (EST) for the removal of common bile duct (CBD) stones. The present study was aimed at assessing the safety and outcome of sequential EPBD following EST for CBD stones. A total of 74 patients (43 females, mean age 41 years) with > or = 10-mm stone(s) in the CBD were selected for the procedure, which included limited EST followed by EPBD with balloon dilators of 10-18 mm in size. Eleven patients h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 21 publications
2
10
2
Order By: Relevance
“…In contrast, we had a 33% mechanical lithotripsy rate in group A and a 32% rate in group B. Compared to previous reports, the frequency of mechanical lithotripsy was markedly higher [24][25][26][27]39] , which might be attributable to the large stones (≥ 15 mm).…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations
“…In contrast, we had a 33% mechanical lithotripsy rate in group A and a 32% rate in group B. Compared to previous reports, the frequency of mechanical lithotripsy was markedly higher [24][25][26][27]39] , which might be attributable to the large stones (≥ 15 mm).…”
Section: Discussioncontrasting
confidence: 81%
“…They reported an 83% success rate in the first session with a 7% rate of mechanical lithotripsy in 58 patients in whom endoscopic removal of bile duct stones using standard EST and balloon/ basket extraction had failed. Recently, multiple published series have shown that the overall first session success rates of stone removal with EBD following EST ranged from 80% to 100% [24,25,27,38] , and these success rates were similar to those of EST. Although some recent studies have reported that the stone clearance rate for the initial session of EBD following EST is high, the outcome for large stone removal by ELBD following EST remains controversial.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Another disadvantage of conventional EPBD is that it is difficult to remove larger stones because the biliary opening is not enlarged to the same degree as with EST [6,7] ; therefore, the application of EPBD is restricted to patients with small stones less than 10 mm in diameter [9] . EPLBD combined with limited EST, which was first proposed to facilitate the removal of large or multiple bile duct stones, has been proven safe and effective in patients with large bile duct stones [27] . EPLBD combined with limited EST enlarged the biliary orifice enough to remove multiple or larger bile duct stones, resulting in an increased success rate of stone removal [28,29] and in decreased use of mechanical lithotripsy [9,12,13,[30][31][32][33] .…”
Section: Resultsmentioning
confidence: 99%